Fostering Motor Vehicle Tax Compliance Through Tax Determinant: with Tax Awareness as a Mediating Variable - Savira, Agnes Dea; Azis, Hellen Nadya Putri; Komara, Acep; Syifaudin, Ahmad (International Journal of Business, Economics, and Social Development, 2025)
This study aims to examine the determinants that influence motor vehicle tax compliance in Cirebon and nearby areas, with tax awareness as a mediating variable. This study analyse the influence of tax information dissemination, tax knowledge requirement, and tax sanction on taxpayer compliance. Quantitative methods were used to gather primary data from 405 respondents through questionnaires. The collected data were analyse using the PLS-SEM technique to investigate the relationship between variables, including the impact of mediation. The results showed that tax information dissemination, tax knowledge requirement, and tax sanction have a significant influence on motor vehicle tax compliance. This study provides practical implications for regional tax authorities, emphasizing the importance of continuous education and socialization, as well as improvements in tax sanction regulations aligned with Law No. 1 of 2022 concerning Financial Relations Between the Central and Regional Governments. This study contributes to the literature by including tax awareness as a mediating construct in the tax compliance model and considering recent policy developments, such as the additional tax levied (Opsen) on motor vehicles. Future research is recommended to expand geographic regions coverage and explore the impact of perceived fairness and overall impact on tax compliance.